A Test of The Risk Perception Attitude Framework as a Message Tailoring Strategy to Promote Diabetes Screening. Issue 6 (12th May 2019) - Rains, Stephen A.; Hingle, Melanie D.; Surdeanu, Mihai; Bell, Dane; Kobourov, Stephen
ABSTRACT: The risk perception attitude (RPA) framework was tested as a message tailoring strategy to encourage diabetes screening. Participants ( N  = 602) were first categorized into one of four RPA groups based on their diabetes risk and efficacy perceptions and then randomly assigned to receive a message that matched their RPA, mismatched their RPA, or a control message. Participants receiving a matched message reported greater intentions to engage in self-protective behavior than participants who received a mismatched message or the control message. The results also showed differences in attitudes and behavioral intentions across the four RPA groups. Participants in the responsive group had more positive attitudes toward diabetes screening than the other three groups, whereas participants in the indifferent group reported the weakest intentions to engage in self-protective behavior.